Projected population-wide impact of antiretroviral therapy-linked isoniazid preventive therapy in a high-burden setting. (1st March 2019) - Kendall, Emily A.; Azman, Andrew S.; Maartens, Gary; Boulle, Andrew; Wilkinson, Robert J.; Dowdy, David W.; Rangaka, Molebogeng X.
Abstract : Objective: Both isoniazid preventive therapy (IPT) and antiretroviral therapy (ART) reduce tuberculosis risk in individuals living with HIV. We sought to estimate the broader, population-wide impact of providing a pragmatically implemented 12-month IPT regimen to ART recipients in a high-burden community. Design: Dynamic transmission model of a tuberculosis (TB)-HIV epidemic, calibrated to site-specific, historical epidemiologic and clinical trial data from Khayelitsha, South Africa. Methods: We projected the 5-year impact of delivering a 12-month IPT regimen community-wide to 85% of new ART initiators and 15%/year of those already on ART, accounting for IPT-attributable reductions in TB infection, progression, and transmission. We also evaluated scenarios of continuously-delivered IPT, ongoing ART scale-up, and lower tuberculosis incidence. Results: Under historical (early 2010) ART coverage, this ART-linked IPT intervention prevented one tuberculosis case per 18 [95% credible interval (CrI) 11–29] people treated. It lowered TB incidence by a projected 23% (95% CrI 14–30%) among people receiving ART, and by 5.2% (95% CrI 2.9–8.7%) in the total population. Continuous IPT reduced the number needed to treat to prevent one case of TB to 10 (95% CrI 7–16), though it required 74% more person-years of therapy (95% CrI 64–94%) to prevent one TB case, relative to 12-month therapy. Under expanding ART coverage, the tuberculosis incidence reduction achieved by 12-month IPT grew to 7.6% (95% CrI 4.3–12.6%). Effect sizes were similar in a simulated setting of lower TB incidence. Conclusions: IPT in conjunction with ART reduces tuberculosis incidence among those who receive therapy and has additional impact on tuberculosis transmission in the population. Abstract : Supplemental Digital Content is available in the text